2005
DOI: 10.1111/j.1365-2672.2005.02668.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of nested PCR assays for the detection of Legionella pneumophila in a wide range of aquatic samples

Abstract: Aims: To compare the sensitivities of two nested PCR assays for the detection of Legionella pneumophila to each other and to the plate counting technique (ISO 11731) in a wide range of aquatic samples. Methods and Results:The nested PCR assay with the primer set LEG 225-LEG 858 revealed 56% of the 46 analysed aquatic samples as being positive for Legionella spp., while the primer set JFP-JRP yielded 98% positive samples. The detection was confirmed by sequencing the PCR products. These results are considerably… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…In contrast, variations in the Legionella population structure were observed over time, with significant changes occurring at the end of June, following a stable phase from mid-May to midJune. In a previous study of microbial communities in a wide range of aquatic samples containing L. pneumophila, no relationship was found between the occurrence of L. pneumophila and the associated microbiota (15). It was observed, however, that the occurrence of L. pneumophila was possible within a certain range of species richness and diversity.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, variations in the Legionella population structure were observed over time, with significant changes occurring at the end of June, following a stable phase from mid-May to midJune. In a previous study of microbial communities in a wide range of aquatic samples containing L. pneumophila, no relationship was found between the occurrence of L. pneumophila and the associated microbiota (15). It was observed, however, that the occurrence of L. pneumophila was possible within a certain range of species richness and diversity.…”
Section: Discussionmentioning
confidence: 98%
“…Strains used in the course of this study were L. pneumophila sg1 (ATCC 33152) and P. putida UWC3. Legionella pneumophila was grown aerobically in Buffered Yeast Extract broth for 72 h at 37°C and supplemented with additional nutrients (Devos et al , 2005b). Pseudomonas putida was grown aerobically in Luria Bertani (LB) broth (Oxoid, Basingstoke, UK) for 24 h at 28°C.…”
Section: Methodsmentioning
confidence: 99%
“…Wellinghausen et al (2001) showed that DNA extraction enabled the detection of legionellae in free-living amoeba, but culturing methods could not detect amoeba. Furthermore, standard culture techniques based on ISO 11731 have numerous limitations (Behets et al, 2007) and several factors complicate the interpretation of plate-counting results (Devos et al, 2005). Cultures can be fastidious due to various factors; for example: the legionellae growth requirements necessitate prolonged incubation periods; the legionellae are difficult to isolate in samples contaminated with high levels of other microbiota, particularly environmental samples; the pre-treatment by acid or heating can lead to underestimates of the number of viable legionellae; viable, but non-culturable bacteria cannot be detected (Catalan et al, 1997;Wellinghausen et al, 2001;Yañez et al, 2005); and Legionella spp.…”
Section: Discussionmentioning
confidence: 99%